Contingencies for Intercultural Dialogue in Virtual Space: An Empirical Research on the Role of Internet in Fostering Intercultural Competences from the Perspective of Migrant Youth - Yafang Wang (Social Work and Society, 2007)
Against the background of the emerging multicultural migration society, acquisition of intercultural competences is getting vitally important for youngsters to actively and effectively engage with intercultural dialogue in a co-existent life context. Contingencies for such intercultural dialogue and to foster intercultural competences of youngsters are opened in virtual space when youth with different ethnic, social and cultural background go online. However, differences in Internet use and competences acquisition as “digital inequality” also exist among youth with different socio-cultural background. This article reports on a quantitative survey of 300 Turkish migrant youth in Germany as empirical sample about how Internet use generally fosters their intercultural competences, what differences exist among them and which indicators can explain the differences. Preliminary findings show that the contingencies of Internet in fostering intercultural competences are still not much employed and realised by Turkish migrant youth. Four online groups connected with bonding, bridging, both (bonding and bridging) and none socio-cultural networks are found out based on the cluster analysis with SPSS. These different networks, from the perspective of social cultural capital, can explain the differences concerning development of intercultural competences among them. It is indicated in this research that many Turkish migrant youth still lack recognition and capabilities to construct their intercultural social networks or relations through using Internet and further to employ the relations as intercultural social capital or social support in their life context. This therefore poses a critical implication for youth work to help migrant youth construct and reconstruct their socio-cultural networks through using Internet so as to extend social support for competences acquisition.